Ethical AI and Responsible Software Development (Journal of human and social sciences, 2025)
The rapid advancement of artificial intelligence (AI) and its integration into software systems have brought transformative benefits to society, while also raising significant ethical concerns. This paper explores the importance of ethical AI and responsible software development in ensuring that technological innovations align with human values and societal well-being. It examines major challenges such as bias, lack of transparency, privacy violations, and environmental impact, highlighting the urgent need for ethical frameworks and best practices in the development and deployment of AI-driven systems. Drawing on existing literature, case studies, and industry guidelines, the study proposes a comprehensive framework for integrating ethical principles into the software development lifecycle (SDLC). The framework emphasizes fairness, transparency, accountability, and sustainability, and offers practical recommendations for developers, organizations, and policymakers. Through this work, the paper contributes to ongoing discussions on ethical AI by promoting a structured approach to responsible software development aimed at fostering trust, inclusivity, and long-term societal benefit.
Keywords: AI; Software Development; Ethical Concerns; Privacy